2022
DOI: 10.31703/gesr.2022(vii-i).08
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Students' Aptitude and their Academic Achievement at Secondary School Level in Khanewal District

Abstract: Students' aptitude is an important factor that determines the students' success in the summative assessment. Similarly, teachers play an important role in the development of scientific attitudes in the personality of students. The main objective of this study was to find out the relationship between students' aptitude and their academic performance at the secondary level. In the same way, it was also investigated what the role of teachers in developing the students' personality attitudes is. The population of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 0 publications
0
16
1
Order By: Relevance
“…Furthermore, this study found that the children of parents with high educational degrees have accomplished much better (87.67% passing percentage) than those of less educated and illiterate parents (56.89% passing percentage). Khan et al (2015) did another study at the secondary level of education with same result. Samples of two hundred students of Grade 10th were taken.…”
Section: Introductionmentioning
confidence: 59%
“…Furthermore, this study found that the children of parents with high educational degrees have accomplished much better (87.67% passing percentage) than those of less educated and illiterate parents (56.89% passing percentage). Khan et al (2015) did another study at the secondary level of education with same result. Samples of two hundred students of Grade 10th were taken.…”
Section: Introductionmentioning
confidence: 59%
“…Despite all the challenges in e-learning, these students tend to complete and academically excel in their studies. Furthermore, Khan, Iqbal, and Tasneem (2015) revealed a significant positive relationship between parents' education levels and students' academic achievements. Studies describe that parents' education plays a vital role in parental involvement, and most of this research has been done with secondary school students (Sui-chu & Williams 1996).…”
Section: Resultsmentioning
confidence: 93%
“…The improvement of parents' academic level usually becomes a reference to be followed by the children in the future, since this behavior is transmitted to students. Furthermore, Khan, Iqbal, & Tasneem (2015) states that those parents who did not have the opportunity to finish their education levels generally do not have the economic, social, and cultural means to help their children to improve their academic performance.…”
Section: Literature Reviewmentioning
confidence: 99%